Creep rupture of the joint between a glass-ceramic sealant and lanthanum strontium manganite-coated ferritic stainless steel interconnect for solid oxide fuel cells. Issue 5 (May 2018) - Lin, Chih-Kuang; Lin, Ting-Wei; Wu, Si-Han; Shiu, Wei-Hong; Liu, Chien-Kuo; Lee, Ruey-Yi
Abstract: Creep rupture is investigated at 800 °C of a joint between a glass-ceramic sealant and a ferritic stainless steel interconnect coated with lanthanum strontium manganite for solid oxide fuel cell application. Results reveal the shear and tensile creep strength of the as-joined, non-aged joint at a rupture time of 1000 h is about 42% and 3% of the average shear and tensile bonding strength, respectively. A thermal aging of 1000 h at 800 °C enhances the creep strength. For both non-aged shear and tensile specimens with a short creep rupture time, fracture mainly takes place in an oxyapatite interlayer which is formed in the joining process. For a medium creep rupture time, fracture site changes to a mixed BaCrO4 /oxyapatite layer. Oxyapatite and BaCrO4 dominate the creep failure mechanism for 1000 h-aged shear specimens, while (Cr, Mn)3 O4 spinel plays a role in the creep failure of 1000 h-aged tensile specimens.